Aplicação de visão de máquina para geração de pontos de trajetória num processo de soldagem robotizado - Paris, Fabricio (2015)
The current paper approaches the development and applying of a machine vision system for obtaining global coordinate points (_, _), regarding images captured from a rectilinear joint from a top of steel sheets to be welded though the MIG/MAG process, ending up on its trajectory and sending it to the control unit to be done by the robot. The stage of the image acquisition is done through the usage of a webcam, which was gauged, this way creating the intrinsic and extrinsic parameters, giving the system more precision on the image capture. A table, projected for the fixing of the steel sheets, characterizing this ways the work reference station, constitutes the specific area for capture of the image. The system of image processing allows us to identify automatically the pixels correspondent to the rectilinear joint for welding, using thresholding through the Otsu Method and morphological algorithms, or so, in a semi-automatic way, through a manual indication of point sequence over the joint image, making the path corresponding to the geometry of it. The position of each point is, then, processed and transformed in Cartesian coordinates, and sent to the robot control unit, which makes the trajectory, simulating a welding process. The transmission to the robot controller is made in a specific protocol, via serial port.